DIDACTIC PROCESS PROJECT METHODS - Mirkhaitova Sohiba (Galaxy International Interdisciplinary Research Journal, 2022)
The formation of the requirements for building a didactic process in a certain sequence means the organization of educational activities using the selected teaching methods in accordance with the goals set for the topic.